Gliptin Accountability in Mucous Membrane Pemphigoid Induction in 24 Out of 313 Patients - Gaudin, Olivier; Seta, Vannina; Alexandre, Marina; Bohelay, Gérôme; Aucouturier, Françoise; Mignot-Grootenboer, Sabine; Ingen-Housz-Oro, Saskia; Bernardeschi, Céline; Schneider, Pierre; Mellottee, Benoît; Caux, Frédéric; Prost-Squarcioni, Catherine (Frontiers in Immunology, 2018)
Mucous membrane pemphigoids (MMPs) and bullous pemphigoid (BP) are autoimmune bullous diseases that share physiopathological features: both can result from autoantibodies directed against BP180 or BP230 antigens. An association has been reported between BP and intake of gliptins, which are dipeptidyl peptidase-IV inhibitors used to treat type 2 diabetes mellitus. Clinical and immunological differences have been reported between gliptin-induced BPs and classical BPs: mucosal involvement, non-inflammatory lesions and target BP180 epitopes other than the NC16A domain. Those findings accorded gliptins extrinsic accountability in triggering MMP onset. Therefore, we examined gliptin intrinsic accountability in a cohort of 313 MMP patients. To do so, we 1) identified MMP patients with gliptin-treated (challenge) diabetes; 2) selected those whose interval between starting gliptin and MMP onset was suggestive or compatible with gliptin-induced MMP; 3) compared the follow-ups of patients who did not stop (no dechallenge), stopped (dechallenge) or repeated gliptin intake (rechallenge); 4) compared the clinical and immunological characteristics of suggestive-or-compatible–challenge patients to 121 never-gliptin–treated MMP patients serving as controls; and 5) individually scored gliptin accountability as the trigger of each patient’s MMP using the World Health Organization–Uppsala Monitoring Center, Naranjo- and Begaud-scoring systems. Seventeen out of 24 gliptin-treated diabetic MMP patients had suggestive (≤12 weeks) or compatible challenges. Complete remission at 1 year of follow-up was more frequent in the 11 dechallenged patients. One rechallenged patient’s MMP relapsed. These 17 gliptin-treated diabetic MMP patients differed significantly from the MMP controls by more cutaneous, less buccal and less severe involvements and no direct immunofluorescence IgA labeling of the basement membrane zone. Multiple autoantibody-target antigens/epitopes (BP180–NC16A, BP180 mid- and C-terminal parts, integrin 64) could be detected, but not laminin 332. Lastly, among the 24 gliptin-treated diabetic MMP patients, five had high (I4–I3), 12 had low (I2-I1) and 7 had I0 Begaud intrinsic accountability scores. These results strongly suggest that gliptins are probably responsible for some MMPs. Consequently, gliptins should immediately be discontinued for patients with a positive accountability score. Moreover, pharmacovigilance centers should be notified of these events.